2010
DOI: 10.1002/ijc.25079
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption‐associated breast cancer incidence and potential effect modifiers: the Japan Public Health Center‐based Prospective Study

Abstract: Epidemiological studies have evaluated whether the impact of alcohol intake on breast cancer risk is modified by use of exogenous estrogens, folate intake, body weight and smoking status, but results have been inconsistent. Further, effect modification by intake of isoflavones and alcohol-induced facial flushing, which are prevalent in Asian populations, have not been investigated. We investigated the association between alcohol intake and breast cancer risk and whether the association is modified by these fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 56 publications
2
44
1
Order By: Relevance
“…In our study, approximately 75% of ever drinkers among the controls drank beer (data not shown in tables). This frequency differed from not only those in American and European populations (Allen et al 2009;Li et al 2009) but also that in the Japanese population (Suzuki et al 2010). In the JHPC study population, the proportion of beer drinkers was low, whereas beverages containing high level of alcohol such as sake and shochu were preferably consumed (Suzuki et al 2010).…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…In our study, approximately 75% of ever drinkers among the controls drank beer (data not shown in tables). This frequency differed from not only those in American and European populations (Allen et al 2009;Li et al 2009) but also that in the Japanese population (Suzuki et al 2010). In the JHPC study population, the proportion of beer drinkers was low, whereas beverages containing high level of alcohol such as sake and shochu were preferably consumed (Suzuki et al 2010).…”
Section: Discussionmentioning
confidence: 50%
“…This frequency differed from not only those in American and European populations (Allen et al 2009;Li et al 2009) but also that in the Japanese population (Suzuki et al 2010). In the JHPC study population, the proportion of beer drinkers was low, whereas beverages containing high level of alcohol such as sake and shochu were preferably consumed (Suzuki et al 2010). Alcoholic beverages contain several chemicals, and it is possible that these chemicals may have different effects on receptor-specific risk (Scoccianti et al 2014).…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations